THE UZBEK LANGUAGE IN THE CONTEXT OFGLOBALIZATION: HISTORICAL LEGACY, CULTURALPOTENTIAL, AND INTERNATIONAL PRESTIGE (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article analyzes the current problems and promising directions of the development of the Uzbek language in foreign countries. In addition, cooperation between Uzbekistan and other countries in the field of language teaching, ongoing cultural and educational projects will be considered. In universities and centers of foreign countries, special attention is paid to the organization of Uzbek language courses, the provision of educational materials and the training of qualified personnel. The article also examines the factors that contribute to the recognition of the Uzbek language within the framework of language policy and international cultural integration